Wireless coding deadbeat power control for doubly-fed induction aerogenerators in smart grid applications - Sguarezi Filho,A. J. (2012)
Smart grids comprise advanced communication infrastructure to provide balance supply, demand, and storage of energy over a region in a much more efficient manner than it is done today. However, in a smart grid, the utilization of wireless technologies for transmitting control information requires a powerful error protection to avoid any serious problems to the energétic plant. With this focus, the work is concerned with a wireless coding deadbeat power control system for a variable speed wind doubly-fed induction generator for smart grid applications.